Decorative laminates based on phenolic resins modified with sodium lignosulfonate and kraft lignin: Evaluation of mechanical properties - Taverna, María E.; Nicolau, Verónica V.; Ollearo, Rocío; Morán, Juan; Frontini, Patricia; Meira, Gregorio; Estenoz, Diana (My University, 2014)
The substitution of phenol in the production of resol-type phenolic resins by environmentally-friendly compounds such as lignin and its derivatives is of great technological and academic interest, due to the similarity between resols and the aromatic structure of lignins. However, lignins must be chemically-modified in order to increase their reactivity toward formaldehyde. In this work, the addition of commercial lignins (sodium lignosulfonate and Kraft-type) as partial replacement of phenol in the resols used for decorative laminates production is experimentally studied. The work involved: the characterization and reactivation of commercial lignins, the industrial synthesis of traditional and modified resols by replacement of 10 and 20% w/w of phenol, the industrial impregnation of Kraft-type papers with the produced resins and the production of laminates at laboratory and industrial scales. The mechanical performance of the laminates was deeply assesed by determining tensile modulus, bending strengh, biaxial flexural impact strenght and Mode- I Interlaminar Fracture Toughness in both processing directions. Modified laminates exhibited mechanical properties comparable with those of traditional laminates, indicating a negligible depreciation of them. Industrial tests were carried out at Centro S.A, San Francisco, Córdoba.
Keywords: decorative laminates; lignins; mechanical properties